Perhitungan Kebutuhan Rak Penyimpanan Berkas Rekam Medis (BRM) 5 Tahun Kedepan Di Gedung Y Rumah Sakit X - Nurul Khatimah Ismatullah (JSN : Jurnal Sains Natural, 2023)
The hospital is a health service institution that provides complete individual health services by providing inpatient, outpatient and emergency services. Plenary Health Services, namely health services that include promotive, preventive, curative, and rehabilitative. The availability of medical record file storage racks in health care facilities is very important in maintaining security and avoiding damage to patient data. The file rack is a place to store archives or medical record documents which aim to facilitate storage and retrieval of medical record documents in the filing room and maintain the confidentiality of medical record documents. The storage of medical record files can exceed the capacity due to the large number of new patient visits and the disproportionate file shelves. Planning or procuring storage racks based on the number of medical record documents stored, the shape of the racks and the size of the storage racks according to ergonomic standards, namely storage racks can be in the form of roll o'pack racks and taking into account the area of an available room. Calculation of the need for shelves is done by using the smallest quadrant calculation. Calculations are made based on the number of new patient visits in the previous 5 years, namely 2018 to 2022. Based on the calculation results, the results show that the need for shelves for the next 5 years is 3 shelves.